RGB Color Image Encryption-Decryption Using Image Segmentation and Matrix Multiplication - J. Aqel, Musbah; ALQadi, Ziad; Ahmed Abdullah, Ammar (International Journal of Engineering and Technology, 2018)
Digital RGB color images are considered as the most widely used data type through the internet, so there is a need for efficient and secure techniques to transmit and protect these digital images and this is a matter of high priority process. Many researchers had developed different techniques to increase the security of image transmission, and most of these techniques suffer from the low speed of the encryption-decryption process. In this paper, a novel technique is proposed that could be used for digital color image encryption-decryption. The performance of this technique is compared with the performance of other techniques and it has shown the advantages of using this technique over other techniques in enhancing the throughput and speed of encryption-decryption process.Â